The association between personality traits and Facebook addiction among adolescent students in a lower middle-income country, Nepal - Prabina Subedi; Surya Bahadur G. C.; Santosh Kumar Gurung; Resam Lal Poudel; Sunita Sharma; Bharat Ram Dhungana (International Journal of Adolescence and Youth)
The role of personality in addictive behaviour among adolescents has been an issue of major concern. This study examined the personality traits on Facebook addiction among adolescent school students in Nepal. A cross-sectional survey of 376 students from grades 9 to 12 employing a self-reported questionnaire incorporating the Bergen Facebook Addiction Scale and Ten-Item Personality Inventory was conducted. The relationship has been examined using binary logistic regression. The results revealed that adolescents exhibiting conscientiousness had a significantly higher likelihood of being addicted to Facebook (AOR: 4.316, 95% CI: 1.182 to 15.762), while those with agreeableness (AOR: 0.421, 95% CI: 0.265 to 0.667) and emotional stability (AOR: 0.099, 95% CI: 0.024 to 0.399) traits had lower odds. Facebook addiction is present among adolescent students in Nepal. Therefore, schools should devise and implement personality development programmes aimed at reducing vulnerability of adolescent students to Facebook addiction and promoting positive social media usage.